2011
DOI: 10.2527/jas.2010-3156
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between chewing behavior, digestibility, and digesta passage kinetics in steers fed oat hay at restricted and ad libitum intakes1

Abstract: The objective of this study was to evaluate the relationships between chewing behavior, digestibility, and digesta passage kinetics in steers fed oat hay at restricted and ad libitum intakes. Four Hereford steers, with an initial average BW of 136 kg, were used in an experiment conducted as a balanced 4 × 4 Latin square with 4 treatments (levels of intake) and 4 periods. Animals were fed lopsided oat hay (Avena strigosa Schreb.) at 4 levels of intake (as a percentage of BW): 1.5, 2.0, 2.5, and ad libitum. Dige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 35 publications
4
17
1
1
Order By: Relevance
“…The observed depressions in the DM and CP digestibility as the level of intake decreased were observed in ruminant species in a previous study (Dias et al, 2011). However, in a meta-analysis published by Huhtanen et al (2009), it was shown that the effect of the feeding level on digestibility is not always consistent; it depends on the dietary chemical and physical characteristics.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The observed depressions in the DM and CP digestibility as the level of intake decreased were observed in ruminant species in a previous study (Dias et al, 2011). However, in a meta-analysis published by Huhtanen et al (2009), it was shown that the effect of the feeding level on digestibility is not always consistent; it depends on the dietary chemical and physical characteristics.…”
Section: Discussionmentioning
confidence: 80%
“…The literature has reported variations in nitrogen excretion in feces (Blaxter and Mitchell, 1948;Lobley et al, 2000;Kiran and Mutsvangwa, 2007;Huhtanen et al, 2009;Dias et al, 2011) and urine (Kiran and Mutsvangwa, 2007;Bohnert et al, 2011;Ghassemi Nejad et al, 2014) due to dietary changes and environmental conditions. The circumstances causing this phenomenon are poorly understood (O'Brien et al, 2010;Bernabucci et al, 2010;Mahjoubi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies assessing effect of different restricted feeding levels on digestibility (Colucci et al, 1981;Okine and Mathison, 1991;Dias et al, 2011) found that OM and NDF digestibility decreased with increasing DM intake. The increased apparent total tract digestibility of OM, NDF and DNDF with reduced feeding level found in this experiment agrees with this, although the feeding level only tended to affect NDF digestibility.…”
Section: Tablementioning
confidence: 99%
“…This variable is a result of the sum of the feeding and rumination times, and it is extremely important to reduce the particle size of the feed, which makes soluble nutrients available for microbial colonization and fermentation (Restle et al, 2009;Dias et al, 2011). In this study, the variation observed in feeding time was not large enough to cause a significant alteration in chewing time per day, which remained constant.…”
Section: Discussionmentioning
confidence: 73%
“…According to Degasperi et al (2003), rumination is a reflex performed by the animal trough mechanical stimuli that are related to the type of diet (fiber content) and the quantity ingested and it happens as a way to reduce the size of the feed particle (Fischer et al, 2002;Dias et al, 2011), and also allows greater production and inoculation of bicarbonate in the digesta, which makes it possible to buffer the ruminal environment (Bailey and Balch, 1961;Michael, 1997). According to Sudweeks et al (1975), reduction of the particle size by grinding reduces the time spent chewing and ruminating, but Beauchemin et al (1994) stated that the way in which the feed is supplied (restricted or ad libitum) may influence the chewing time during ingestion, and consequently change the total time used for rumination.…”
Section: Discussionmentioning
confidence: 99%